Development of Mathematics Teaching Materials to Improve Students' Critical Thinking Ability with Realistic Mathematics Learning Approach (PMR) Class VIII MTsS PP Al - Qomariah Galang - Nur Asiyah; Pargaulan Siagian; KMS. M. Amin Fauzi (BIRCU, 2021)
This study aims to determine the validity, practicality and effectiveness of the developed teaching materials, as well as to determine the improvement of students' critical thinking skills using the developed teaching materials. Data obtained through the validation sheet of teaching materials, observation sheets, student response questionnaires, and critical thinking skills test instruments. This study uses the 4-D development model Thiagarajan, Semmel and Semmel (1974) by developing mathematics teaching materials with a realistic mathematics approach. Based on the results of the validity of the learning tools developed, it was included in the valid category with an average value of the total validity of students' books of 4.50, LKPD of 4.62 and the critical thinking ability test in the valid category. The effectiveness of learning devices that meet the effective criteria with the achievement of student learning completeness with a classical completeness percentage of 86.1%., Active student activities meet the ideal time tolerance criteria set, and student responses to learning devices are in good categories. And the average increase in students' critical thinking skills from trial I to trial II was 0.34 points with an increase in classical learning completeness of 17.35%.